2001
DOI: 10.1103/physrevb.65.033405
|View full text |Cite
|
Sign up to set email alerts
|

Hot-complex-mediated abstraction and desorption of D adatoms by H on Si(100)

Abstract: The collision-induced associative desorption ͑CID͒ and abstraction ͑ABS͒ of D adatoms by H have been studied on the Si͑100͒ surfaces. D 2 CID exhibits a feature common to that of a thermal desorption from a dideuteride phase. HD ABS proceeds along an apparently second-order kinetics rather than a first-order kinetics with respect to surface D coverages. The ABS cross section is about 6 Å 2 , extremely large compared to the theoretical values. Both of the direct Eley-Rideal mechanism and the hot-atom mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…This is the extended version of the hot-complex mediated D abstraction by H, which was proposed by Hayakawa et al for the first time in the reaction system H(g) + D/Si(1 0 0) ! HD [13]. As was supposed in their studies, longly lived hot atoms are not allowed on the Si surfaces, but they are promptly converted to an immobile hot-complex.…”
Section: Kinetic Mechanismmentioning
confidence: 93%
See 1 more Smart Citation
“…This is the extended version of the hot-complex mediated D abstraction by H, which was proposed by Hayakawa et al for the first time in the reaction system H(g) + D/Si(1 0 0) ! HD [13]. As was supposed in their studies, longly lived hot atoms are not allowed on the Si surfaces, but they are promptly converted to an immobile hot-complex.…”
Section: Kinetic Mechanismmentioning
confidence: 93%
“…Recombinative desorption of D adatoms from D-terminated Si surfaces can be also induced by H atoms [13,14]. The recent progress in the study of the H-induced D 2 desorptions from D-terminated Si(1 0 0) surfaces shows up that the desorption is induced by adsorption of H atoms onto a (3 · 1) monodeuteride/dideuteride domain on the (2 · 1) monodeuteride Si surfaces [15,16].…”
Section: Introductionmentioning
confidence: 98%
“…So far, the abstraction reactions have been studied mainly from a kinetics point of view [9][10][11][12][13][14][15][16][17][18][19][20][21][22] rather than from a dynamics point of view. [23][24][25][26][27] Dinger, Lutterloh, and Küppers 9,20 reported that the reactions of Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…1͒ has a serious drawback for predicting the kinetic mechanisms for HD and D 2 desorptions in the abstraction of D by H on Si͑100͒. In a series of pub- lished papers, we suggested that the hot atom mechanism is ruled out on the basis of several experimental facts: ͑i͒ the unexpectedly high reaction order for the HD ͑approximately second-order͒ and D 2 ͑approxi-mately fourth-order͒ desorptions; 8 ͑ii͒ the strong temperature dependence of efficient D 2 desorption; 9 and ͑iii͒ the efficient adsorption of H atoms even onto D-terminated Si atoms. 10 To reconcile these facts we have proposed a hot complex mechanism by which H atoms are first bound in the excited states of chemisorption in a DSi-SiD unit.…”
mentioning
confidence: 99%
“…10 To reconcile these facts we have proposed a hot complex mechanism by which H atoms are first bound in the excited states of chemisorption in a DSi-SiD unit. 9,11 As evidenced by the efficient formation of dihydrides, 10 the reaction of H atoms with terminated Si atoms is one of the most important energy dissipation channels when H atoms are trapped on a Si surface. This energy dissipation should be seriously taken into account when the hopping of hot H atoms across D-terminated Si͑100͒ surfaces is treated.…”
mentioning
confidence: 99%